Antropomorfisme Brand: Kampanye Digital Pencegahan Covid-19 Oleh Traveloka - Puspita Ayu Shavira (Jurnal Ilmu Komunikasi, 2020)
Covid-19 has become a pandemic and the government is still trying to break the chain of this virus. Changes occur in many sectors in society, one of which is the accommodation and tourism sector. Traveloka, as one of the unicorn startups included in the accommodation and tourism sector, was also affected by the impact of Covid-19. In response to this complicated situation, Traveloka has adapted creatively by creating its latest advertisement in the form of a Covid-19 campaign. Traveloka tries to highlight the anthropomorphic side. The focus of this research is how Traveloka as a startup unicorn is able to capture millions of attention through personal closeness through anthropomorphism. The purpose of this research is to find out how brand anthropomorphism is in the Traveloka digital campaign as a social movement for the prevention of Covid-19. This study used a qualitative-descriptive approach by collecting data from in-depth interviews, observations, and literature studies. The result of this research is Traveloka uses anthropomorphism elements as an advertising attraction with anthropomorphic elements to generate sympathetic feelings from informants. This sympathetic feeling led to the informants' prosocial action to participate in fighting Covid-19.